Subscribers’ social factors and adoption of self-service platforms in Delta State - Peter Ikpeazu (Southeast Asian Journal of Service Management, 2025)
Abstract. This study aims to examine the socio-economic factors influencing the use of digital service delivery touch-points among MTN and DStv subscribers in Delta State, Nigeria. Specifically, it investigates the effects of peer group influence, awareness, and demographic characteristics such as gender, age, educational qualification, and occupation on the usage of mobile self-service applications. A cross-sectional survey design was employed, and data were collected through structured questionnaires distributed to 381 MTN and DStv subscribers. The data were analysed using descriptive statistics and inferential statistics with the aid of SPSS. The findings of this research proved that peer group influence, awareness, and demographic characteristics have significant effects on the usage of self-service applications among MTN and DStv subscribers.